Impact Migrasi Aplikasi BSI Mobile Ke BYond By BSI: Untuk Nasabah Bank Syariah Indonesia (BSI) KCP Jember Karimata - Muhammad Ahsanul Imam; Erfan Efendi; Baharudin Rachman; Aldila Ersaputri; Wildan Khisbullah Suhma (GLOBAL SCIENTS PUBLISHER, 2025)
The development of information and communication technology has brought significant transformation in the banking sector, especially through the introduction of mobile banking services. Bank Syariah Indonesia (BSI) became a pioneer with the launch of BSI Mobile in February 2021, which allows customers to make banking transactions easily through smartphones. However, to improve the quality of service, BSI launched a new application, BYond by BSI, as a replacement for BSI Mobile. The app is designed to provide a more modern, fast, and efficient digital banking experience, as well as integrate social and spiritual features, such as zakat services and prayer timers. This study aims to analyze the impact of the migration from BSI Mobile to BYond by BSI on consumer comfort and satisfaction at BSI KCP Jember Karimata. The research method used is qualitative descriptive with direct observation. The results of the study show that BYond by BSI has managed to attract more than 3 million active users in the two months after the launch, which reflects the positive response from customers. This transformation is in line with the government's commitment to encourage digitalization in the Islamic banking sector and is expected to strengthen BSI's position as a leading Islamic bank in Indonesia, with a target of reaching 10 million users by the end of 2025.